VIVÊNCIAS E ESTÁGIOS NA REALIDADE DO SISTEMA ÚNICO DE SAÚDE NA CIDADE DE SANTA ROSA NO RIO GRANDE DO SUL - Kusiack, Adriana; Fritzen, Daiana I.; Santosi, Elton D. C. d.; Zawacki, Fábio P.; Cantarelli, Gabriela; Subutzki, Jordana; Steiernagel, Laís R.; Ubessi, Liamara D.; Righi, Liane B. (Salão do Conhecimento, 2013)
Resumo